Analisis Kandungan Flavanoid Daun Sambang Darah (Excoecaria cochinchinensis L) - Ariani H. Hutuba; A. Mu'thi Andy Suryadi; Faramita Hiola (State University of Gorontalo, 2023)
Flavonoids are chemical compounds derived from plants which are a group of secondary metabolites. Flavonoids Flavonoid compounds are polyphenolic compounds that have 15 carbon atoms arranged in a C 6 -C 3 -C 6 configuration, namely two aromatic rings connected by 3 carbon atoms that can or cannot form a third ring. Flavonoids are widely distributed in angiosperms, gymnosperms, and pteridopites. These flavonoids provide physiological and pharmacological effects on living things. The purpose of this study was to identify the flavonoid compounds present in the leaf extract of the blood sambang plant (Excoecaria cochinchinensis L). In this study, a multilevel maceration extraction was used using n-hexane, ethyl acetate and methanol solvents and then the filtrate was evaporated using an evaporator. Positive phytochemical screening results indicated the presence of flavonoids in methanol extract and negative in n-hexane and ethyl acetate extracts. From the methanol extract, TLC was carried out with an eluent ratio of methanol ethyl acetate (8: 2), it was obtained the separation of two stains where one of the stains had the same Rf value as the Rf value of flavonoids, then performed a UV-Vis spectrophotometric analysis resulting in three absorption wavelengths, namely band I (350 nm) and band II (255 nm and 267 nm). the spectrum obtained is a class of flavone compounds.